2010
DOI: 10.1111/j.1460-2695.2010.01531.x
|View full text |Cite
|
Sign up to set email alerts
|

A stochastic fatigue damage model for composite single lap shear joints based on Markov chains and thermoelastic stress analysis

Abstract: A B S T R A C T Quantitative damage detection in composite single lap joints during fatigue is difficultand not practical with many traditional experimental methods. The objective of this study is to combine a new experimental analysis method with existing stochastic models that is capable of taking the scatter inherent in composite fatigue data into account for better representation of damage evolution in single-lap joints. This study presents a new quantitative approach where thermoelastic stress analysis (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The Markov chain model used in the present study includes a probability transfer matrix (PTM), shown in Equation 1, that represents a load cycle. The variables p 1 and q 1 are, respectively, the retention probability and the transition probability 25,26,28,39 . A sample can therefore pass from an initial state b 1 to the next state b 2 with probability q 1 but cannot return to a previous state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Markov chain model used in the present study includes a probability transfer matrix (PTM), shown in Equation 1, that represents a load cycle. The variables p 1 and q 1 are, respectively, the retention probability and the transition probability 25,26,28,39 . A sample can therefore pass from an initial state b 1 to the next state b 2 with probability q 1 but cannot return to a previous state.…”
Section: Methodsmentioning
confidence: 99%
“…It has been applied to composite materials 25–27 while showing life prediction skills. The models can be made more complex by using a time transformation, 25,28 by optimizing the number of parameters, 29 and/or by calculating them iteratively 30 . All three of these techniques increase the precision of an already well‐fitted model.…”
Section: Introductionmentioning
confidence: 99%
“…It was almost exactly from the beginning of the test that the crack initiation occurred at both ends of flat joints. According to the literature, crack propagation dominates the fatigue life of bonded SLJs, where the crack is initiated after 15% of the entire fatigue life …”
Section: Fatigue Tests With Different Load Levelsmentioning
confidence: 99%
“…According to the literature, crack propagation dominates the fatigue life of bonded SLJs, where the crack is initiated after 15% of the entire fatigue life. [49][50][51][52][53] After appearing and extending rapidly for a short distance, this crack grew in a stable manner until the final failure of the joint. When around 0.4-0.6 of the fatigue crack propagated along the bond length, sudden fracture occurred in all the specimens.…”
Section: Flat Jointsmentioning
confidence: 99%
“…Markov chains were first applied to fatigue modeling in composites by Rowatt et al [17] as an extension of the pioneering work of Bogdanoff et al [16]. Other relevant examples of Markov chains models for fatigue in composites are found in [18][19][20][21] while for metals in [22][23][24][25][26][27][28]. More applications and theoretical insight about stochastic cumulative damage models are provided in [29][30][31].…”
Section: Introductionmentioning
confidence: 99%